SAFE INDUCED ABORTION: KNOWLEDGE AND ATTITUDE AMONG MEDICAL INTERNS OF ADDIS ABABA UNIVERSITY - Lakew, Kalkidan; Worku, Dawit (Ethiopian Journal of Reproductive Health, 2020)
Background Ethiopia has become one of the countries that have shown a significant reduction in maternal mortality in relation to unsafe abortion after the revision of the abortion law that resulted in the legalization of abortion in certain circumstances since 2005. Medical interns are the future physicians who will encounter many women in need of safe abortion in their careers. Their knowledge and attitude towards induced abortion will determine their practice. Methods A cross-sectional descriptive study was conducted using a self-administered questioner that was distributed among all 240 medical interns of Addis Ababa University, School of Medicine between September and October 2018. Result Two hundred and five medical interns have participated in the study with an 85.4% response rate. Females were 35.1% and male. The majority of the study participants, 63.1%, were followers of Orthodox Christian religion. Only 66% of the medical interns have the knowledge of all the indications for which the Ethiopia Abortion law permits safe abortion services. Ninety-six percent (96%) of the interns believe safe abortion is important but only 54% of them are willing to provide safe abortion services by themselves. The most common reason reported for not willing to provide a safe abortion service is religion. Conclusion The study shows that most medical interns are aware of one or more of the indications to providing safe abortion under the current Ethiopian abortion law and that most have a positive attitude towards the importance of safe abortion services. There is a palpable knowledge gap regarding the abortion law and the technique of termination of pregnancy. Further integration of training on safe abortion methods and abortion law into the training of medical students can alleviate this knowledge gap. Keywords: Medical interns, induced abortion, knowledge and attitude